Insight into the influence of small organic molecules on the wettability of coal. (15th June 2021) - Ji, Huaijun; Peng, Xianqi; Yao, Jian; Mao, Yingnan; Hou, Yi; Sheng, Zhenke
Highlights: The change of different surface functional groups after extraction was analyzed. The influence of small organic molecules on wettability were explored. The effect of surface functional groups on wettability were analyzed. Abstract: Small organic molecules are important parts of coal, but their effects on the surface structure and wettability of coal have rarely been studied. Long-flame coal and coking coal were selected as experimental coal samples in this study. Tetrahydrofuran was used to extract small organic molecules from coal. FTIR was used to detect the changes in functional groups before and after extraction. The wettability test was used to determine the changing conditions in the wettability of coal before and after extraction. The results showed that the contents of various functional groups on the coal surface decrease after the small organic molecules were dissolved. Moreover, after extraction, the wettability of long flame coal was reduced by 49.6%, and the wettability of coking coal was reduced by 30.8%. Molecular simulation was used to study the effect of functional groups on coal wettability. The benzene ring, methyl groups, carboxyl groups, and hydroxyl groups were connected to the graphite surface to construct adsorption models to simulate the adsorption of water molecules. In each unit cell, the adsorption of water molecules increased by 12.076, 4.133, 13.273 and 28.603 due to the existence of benzene rings, methyl groups, carboxyl groups and hydroxyl groups, respectively. Wettability was further enhanced by oxygen-containing functional groups, such as hydroxyl and carboxyl groups, mainly due to the existence of hydrogen bonds. Therefore, after extraction, oxygen-containing functional groups on the surface of the coal were dissolved along with the dissolution of small organic molecules, which was the main reason for the decreased wettability.